RT-Train: A Real-Time Tracking System for Public Train in Malaysia - Yong, Ng Seng; Chong, Mien May; Ping, Lai Chew (Journal of Applied Technology and Innovation, 2019)
Real-time Public Train Tracking System is a system for the train user to check the train schedule, track the upcoming train’s location in real-time, and receiving announcement via push notification. In this paper, a new prototype of the Real-Time Public Train Tracking System called “RT-Train” was introduced. This proposed system can reduce the congestion of train users and allows train users to know the accurate train schedule and the real-time location of the train. Besides, it allows the train users to receive the push notification if the train is delayed. In this paper, we had also included an Abstract Architecture in explaining the system flow of the proposed system by using use case diagram. In the testing stage, four (4) major sub stages includes Unit Testing, Integration Testing, System Testing and User Acceptance Testing (UAT) have been done. From the results, all the actual results are same as the expected results. As a conclusion, the proposed system has achieved all the objectives that aimed by us.